N Gene Mutations of SARS-CoV-2 and their Association with Variants and Pathogenicity among Iraqi Patients - Maeh, Raghad KH.; Fadhil, Hula Y. (Iraqi Journal of Science, 2026)
Global spreading happened for a novel coronavirus called SARS-CoV-2 that emerged in 2019. The viral genetic diversity studies help us to comprehend the virus’s transmission, pathogenesis, and epidemiology. The main aim of this study is to improve the dataset of Iraqi SARS-CoV-2 mutation, monitor virus spread and evolution, and identify possible mutation patterns. As seen from this study, all the sequenced positive samples had mutations in variable regions of N gene. It was discovered in 23 local isolates that 18 were Omicron associated with moderate infections, accounting for 61.1%. The remaining isolates comprised three Alpha and two Beta variants, all associated with severe infection, caused mutation leading to alteration of amino acids and nuclear proteins including transition transversion deletion etc. In addition, there is an altered coiled structure presented by the Alpha variant. The phylogenetic tree demonstrates higher similarity with other local isolates and very little diversity between references and worldwide isolates. In conclusion, the analysis of the N gene variable region brings important data on mutations that are useful for detecting variants and developing new detection assays against coronavirus-causing COVID-19 disease, referred to as SARs-Cov2. These findings may contribute to improved treatment options for people suffering from COVID-19 and vaccine development.